Employment of Oligodeoxynucleotide plus Interleukin-2 Improves Cytogenetic Analysis in Splenic Marginal Zone Lymphoma. (21st May 2011) - Bardi, Antonella; Cavazzini, Francesco; Rigolin, Gian Matteo; Tammiso, Elisa; Volta, Eleonora; Pezzolo, Elisa; Formigaro, Luca; Sofritti, Olga; Daghia, Giulia; Ambrosio, Cristina; Rizzotto, Lara; Abass, Awad E.; et al.
Abstract : To compare the efficiency of novel mitogenic agents and traditional mitosis inductors, 18 patients with splenic marginal zone lymphoma (SMZL) were studied. Three cultures using oligodeoxynucleotide (ODN) plus interleukin-2 (IL-2), or TPA, or LPS were setup in each patient. Seventeen/18 cases with ODN + IL 2 had moderate/good proliferation (94, 4 % ) as compared with 10/18 cases with TPA and LPS (55 % ) (P = .015 ); 14/18 (77, 7 % ) cases with ODN + IL 2 had sufficient good quality of banding as compared with 8/18 cases (44, 4 % ) with TPA and LPS. The karyotype could be defined from ODN + IL 2 -stimulated cultures in all 18 patients, 14 of whom (77, 7 % ) had a cytogenetic aberration, whereas clonal aberrations could be documented in 9 and in 3 cases by stimulation with LPS and TPA, respectively. Recurrent chromosome aberrations in our series were represented by aberrations of chromosome 14q in 5 patients, by trisomy 12 and 7q deletion in 4 cases each, and by abnormalities involving 11q and 13q in two cases each. These findings show that stimulation with ODN + IL 2 offers more mitotic figures of better quality and results in an increased rate of clonal aberrations in SMZL, making this method ideal for prospective studies aiming at the definition of the prognostic impact of cytogenetic aberrations in this disorder.